Pengaruh Kepemimpinan Kepala Sekolah dan Kelengkapan Fasilitas Terhadap Kinerja Guru di MBI Amanatul Ummah Pacet Mojokerto - Abdul Wali Garai (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research is research using deductive and inductive methods and a quantitative approach. This method starts with a theoretical framework, expert views, or researchers' descriptions based on their experience, and then turns into cases and recommended solutions to obtain justification or evaluation in the form of empirical data in the field. This research uses a multiple linear regression analysis method using a computer program, namely the statistical package for the social science (SPSS) software version 22. Research results (1) Principal Leadership Development: It is necessary to carry out a leadership development program for school principals so that they can develop effective leadership skills. School principals need to be able to inspire and motivate their teachers to improve the quality of their teaching and performance. (2) The government and educational institutions need to pay special attention to maintaining and improving learning support facilities in schools. Facilities such as learning facilities, laboratories, libraries, technology and other infrastructure must be improved so that teachers can provide more effective teaching. (3) Teachers also need to be empowered through training and professional development programs. Teachers need to be given opportunities to develop their teaching skills and adopt innovative and effective teaching methods. Leadership is a process that influences structured group activities to achieve common goals,